Some Addition Reactions of 3-Arylidene-5,6-diphenyl-1,2,4-triazenes - Abdel-Rahman, R.M.; Fawzy, M.M. (Asian Journal of Chemistry, 2010)
Addition of various functional compounds such as butane-1-thiol, 2-methyl-1,3-butadiene, thioglycolic acid, chloroacetyl chloride, sodium ethylate, thiosalicyclic acid, p-chlorothiophenol and also the reduction with zinc-acetic acid to 3-arylidene 5,6-diphenyl-1,2,4-triazenes (IIa-d) have been studied. The structural assignments of all the new products were based on elemental analysis, characteristic IR and PMR data.